Domesticating a religious import : the Jesuits and the inculturation of the Catholic Church in Zimbabwe, 1879-1980 - Creary, Nicholas M. (Fordham University Press, 2011)
Ranging over the century after Jesuit missionaries first settled in what is now Zimbabwe, this title reveals two simultaneous and intersecting processes: the Africanization of the Catholic Church by African Christians and the discourse of inculturation promulgated by the Church.